O processo de internacionalização de uma instituição de ensino superior : o caso da Pontifícia Universidade Católica do Paraná - Lago, Sandro Luis do (2015)
The internationalization of higher education institutions is not a new phenomenon. It can be found in the form of scientific and cultural knowledge exchange since the Middle Ages. In recent decades, the phenomenon of globalization has deeply affected higher education. In response to this phenomenon, higher education institutions have sought the internationalization of its activities. However, this internationalization process is complex, and is influenced by various internal and external elements to the institution. This study aimed to understand how is it happen the process of internationalization of higher education institution. For this purpose, a descriptive study was conducted with a qualitative approach, developed through single case study at the Pontifical Catholic University of Paraná (PUCPR). To develop the research, semi-structured interviews were used with managers directly connected with the process of internationalization and secondary data obtained from the documentary information. Data analysis was performed through content analysis and, as a theoretical basis for data analysis, was used Knight's internationalization model (1994; 2008). Based on the research's results can be seen that the PUCPR internationalization process occurred gradually and today internationalization is crafted with programs and strategies aimed at internationalization of education and research, such as exchanges and the development of joint researches. To give support to these programs and strategies, and create conditions for the international dimension is actually integrated into the institution, organizational strategies are used to improve governance, operations, structures and services support. Moreover, the existence of strategic planning for internationalization and evaluation system of the results has allowed the continued development of internationalization.